A global review demonstrating the importance of nocturnal pollinators for crop plants. Issue 12 (3rd October 2022) - Buxton, Max N.; Gaskett, Anne C.; Lord, Janice M.; Pattemore, David E.
Abstract: Pollinating insects are critical to ecosystem stability and food security. Concerns about the impact of insect declines have therefore seen increased research on the role of wild pollinators in cropping systems. However, this research has predominantly focused on diurnal pollinators such as bees and flies, leaving the role of nocturnal pollinators poorly understood in comparison. Here, we review the literature on nocturnal pollinators of food crops and medicinal plants by undertaking an abstract, title, and keyword literature search in Web of Science Core Collection [v.5.32]. We found interactions recorded between plants and nocturnal pollinators for 52 plant families, with Cactaceae, Fabaceae and Asparagaceae being mentioned most frequently in the context of nocturnal pollination. We identified 81 animal families that behave as nocturnal crop pollinators, with Sphingidae and Noctuidae moths and Phyllostomidae bats being mentioned most frequently. The evidence to support claims of pollination by nocturnally active animals varied in strength and mostly involved observations of flower visitation or pollination being inferred based on floral traits. There was a lack of strong experimental evidence. Detailed experimental work, such as pollinator exclusion experiments, is therefore required to corroborate the patterns we have discovered. Our review is biased towards publications in the English language, but despite this our study shows tropical regions such as Brazil appear to be hotspots for nocturnal crop pollination. Policy implications . Our findings suggest that nocturnal pollinators visit a large range of crop plants, and may be more important to ecosystem function and food production than currently thought. Current policies in cropping systems implemented to protect bees, such as regulations on pesticide use, are unlikely to also protect nocturnal pollinators. As we develop a better understanding of the importance of nocturnal pollinators for crop plants, many of these regulations may need to be updated to ensure pollination service is not being compromised. Abstract : Our findings suggest that nocturnal pollinators visit a large range of crop plants, and may be more important to ecosystem function and food production than currently thought. Current policies in cropping systems implemented to protect bees, such as regulations on pesticide use, are unlikely to also protect nocturnal pollinators. As we develop a better understanding of the importance of nocturnal pollinators for crop plants, many of these regulations may need to be updated to ensure pollination service is not being compromised.